Atypical presentation of COVID-19: Chronic bilateral testicular pain with lower extremity peripheral polyneuropathy, case report - Aníbal Salazar (Elsevier, 2022)
In context of COVID-19 pandemic, there has been different presentations of the infection. The relationship of testicular pain with COVID-19 has not been extensively studied. We present a 31 years old male, with SARS-COV-2 infection, repeatedly consulting for intermittent bilateral testicular pain. Two months later he reported acute loss sensibility and pain in extremities, being diagnosed with axonal fine fiber polyneuropathy. Although the presence of SARS-COV-2 in testis remains controversial, there is a potential orchiepididymitis risk due to viral binding to ACE2 receptor in testicle, and also could induce systemic vasculitis as another possible cause of orchitis.